Analisis Kelayakan Finansial Usaha Ternak Puyuh Petelur Di Kecamatan Payakumbuh Kabupaten Lima Puluh Kota - Ningsih, Yurma; Nofrianil, Nofrianil; Nefri, John (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Kecamatan Payakumbuh is the district with the highest number of quail populations in Kabupaten Lima Puluh Kota. In its cultivation, there are several obstacles, one of which is the rising price of feed and the low price of quail eggs, so that the income received by farmers is low. An alternative used by breeders is to use relatively cheaper mortar feed. This study aims to (1) Analyze how much income the laying quail business in Kecamatan Payakumbuh, Kabupaten Lima Puluh Kota and (2) Analyze whether the laying quail business in Kecamatan Payakumbuh, Kabupaten Lima Puluh Kota is feasible to run. The data used is in the form of primary data and secondary data. The study was conducted in March-April in Kecamatan Payakumbuh, Kabupaten Lima Puluh Kota. The method of its analysis is income and financial feasibility. The method of analysis is the analysis of income and financial feasibility. Based on the results of the study can be concluded: (1) The total business income of laying quail is IDR 870,344,858 for one period, (2) Based on 4 sub-categories of investment feasibility using R/C Ratio, PP, NPV and IRR of laying quail business in Payakumbuh District is worth cultivating, subcategories are determined based on the total quail population, (3) Category 1 has an R/C ratio of 1.76, PP of 0.34, NPV of Rp 612,634,681 and IRR of 291%, (4) Category 2 has an R/C ratio of 2.45, a PP value of 0.25, an NPV of Rp 1,269,965,862 and an RR of 408%, (5) Category 3 has an R/C ratio of 2.13, PP of 0.25, NPV of Rp 1,640,979,042 and IRR of 691%, (6) Category 4 has an R/C ratio of 2.16, PP of 0.17, NPV of Rp 1,933,060,814 and IRR of 584%.